Trends In The Development Of Auditing Activities In Uzbekistan - Mutabar Khodjayeva; Hashimova Sevara Sultanhoja Kizi (Zien Journals, 2022)
The domestic theory and practice of audit, as a developing institution of the legal economy, is taking shape in the face of serious competition. Quite a few rather large domestic audit organizations have appeared that provide an almost complete range of audit services, domestic organizations have gained relevant experience in the field of audit.
Keywords: domestic; theory; practice; services